Enhancing the stability and catalytic efficiency of alkyl halide dehalogenase through poloxamer temperature-sensitive gel - Jianjun Zhu; Jun Zhang; Feng Gong; Qiong Yu; Xuan Guo; Yu Wang (PLoS ONE, 2025)
Dha A, a biocatalyst with pronounced efficacy in the degradation of mustard gas, is constrained by its inherent instability, which impedes its broader application. In this study, we encapsulated Dha A within a poloxamer-based thermosensitive hydrogel, a widely utilized protein carrier, to assess its physicochemical characteristics, catalytic performance, and stability enhancement. The Dha A-loaded thermosensitive gel (Dha A@TSG) exhibited interactions between Dha A and poloxamer molecules via hydrogen bonding, with an optimal gelation temperature of 25°C. This encapsulation strategy significantly enhanced the solubility and catalytic efficiency of the mustard gas mimic, bis(2-chloroethyl) ether, surpassing the performance of the free Dha A solution. At 32°C, the poloxamer molecules within Dha A@TSG formed a tightly packed stereostucture, which substantially improved the storage and thermal stability of Dha A. Collectively, our findings offer valuable technical insights into the stabilization and catalytic efficiency enhancement of Dha A through the employment of poloxamer thermosensitive gels.